2017
DOI: 10.1002/adma.201703284
|View full text |Cite|
|
Sign up to set email alerts
|

Theranostic 2D Tantalum Carbide (MXene)

Abstract: The large-dimensional and rigid ceramic bulks fabricated by high-temperature solid-phase reaction and sintering have never been considered for possibly entering and circulating within the blood vessels for biomedical applications, especially on combating cancer. Here, it is reported for the first time that MAX ceramic biomaterials exhibit unique functionalities for dual-mode photoacoustic/computed tomography imaging and are highly effective for in vivo photothermal ablation of tumors upon being exfoliated into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
331
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 486 publications
(348 citation statements)
references
References 52 publications
15
331
0
2
Order By: Relevance
“…[9] The first synthesis of monolayer silicene was achieved on Ag(111) surface. [17] By analogy, 2D silicene, a hexagonal honeycomb lattice featuring non-planar buckled configuration, could be supposedly synthesized from the precursor Zintl-phase silicide (e.g., CaSi 2 ) via a topochemical deintercalation process of selective Ca-removal. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9] The first synthesis of monolayer silicene was achieved on Ag(111) surface. [17] By analogy, 2D silicene, a hexagonal honeycomb lattice featuring non-planar buckled configuration, could be supposedly synthesized from the precursor Zintl-phase silicide (e.g., CaSi 2 ) via a topochemical deintercalation process of selective Ca-removal. …”
mentioning
confidence: 99%
“…However, these as-synthesized silicene derived from epitaxial growth methods encounter three major drawbacks: scalable synthesis limitation, nonuniformity in vertical scale, and great difficulties in the transfer of layered materials from substrates. [17] By analogy, 2D silicene, a hexagonal honeycomb lattice featuring non-planar buckled configuration, could be supposedly synthesized from the precursor Zintl-phase silicide (e.g., CaSi 2 ) via a topochemical deintercalation process of selective Ca-removal. [16] Fortunately, these issues have been overcome by using selective extraction method upon converting MAX-phase layered compounds to versatile 2D MXene-phase nanosheets.…”
mentioning
confidence: 99%
“…[15] Our results clearly indicated that the as-prepared photothermal electrode could efficiently raise the local temperature of the bioelectrode to approximately 30 8Cf rom low temperatures( i.e.,1 0, 15, and 20 8C) under simulated sunlight illumination,w hich enablede fficient microbial energy harvesting from the BESs at low operating temperatures. The photothermal electrode was prepared by coating MXene (Ti 3 C 2 T x )o nto ac arbon felt (CF) electrode (CF/MXene).…”
Section: Introductionmentioning
confidence: 71%
“…[106] The narrow bandgap of Ti 3 C 2 T x flakes indicates that Ti 3 C 2 T x flakes are semiconductors. [112] Apart from the properties mentioned above, MXenes show numerous attractive properties, such as adsorption, [111,113,114] ferromagnetism, [30,115] antibacterial activity, [116,117] thermoelectric property, [118] gas separation performance, [119] photothermalconversion capability, [120] etc. The conductivity of the Ti 3 C 2 T x flakes can reach as high as 6500 S cm −1 .…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%